2006
DOI: 10.1074/jbc.m601451200
|View full text |Cite
|
Sign up to set email alerts
|

Endosomal Acidification and Activation of NADPH Oxidase Isoforms Are Upstream Events in Hyperosmolarity-induced Hepatocyte Apoptosis

Abstract: Hyperosmotic exposure of rat hepatocytes induced a rapid oxidative stress (ROS) response as an upstream signal for proapoptotic CD95 activation. This study shows that hyperosmotic ROS formation involves a rapid ceramide-and protein kinase C (PKC)-dependent serine phosphorylation of p47 phox and subsequent activation of NADPH oxidase isoforms. Hyperosmotic p47 phox phosphorylation and ROS formation were sensitive to inhibition of sphingomyelinases and were strongly blunted after knockdown of acidic sphingomyeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(88 citation statements)
references
References 78 publications
(145 reference statements)
3
85
0
Order By: Relevance
“…Qin et al [26] have shown that Angiotensin II induced apoptosis in H9c2 cells via an increase in cytoplasmic and apparent nuclear p47 phox expression as determined by western blot and immunocytochemistry, which resulted in intracellular ROS production; however, the effect on other subunits such as NOX2 was not determined. Reinehr et al [27] have shown in p47 phox knock-out mice that hepatocytes no longer produced ROS. Furthermore, Heymes et al [28] found an increase in translocation of p47 phox to the sarcolemmal membrane of cardiomyocytes in failing human hearts compared to non-failing hearts, which coincided with increased membrane and intracellular gp91 phox expression, analyzed by immunohistochemistry, which could suggest that both p47 phox and gp91 phox are necessary for cardiomyocyte damage.…”
Section: Discussionmentioning
confidence: 99%
“…Qin et al [26] have shown that Angiotensin II induced apoptosis in H9c2 cells via an increase in cytoplasmic and apparent nuclear p47 phox expression as determined by western blot and immunocytochemistry, which resulted in intracellular ROS production; however, the effect on other subunits such as NOX2 was not determined. Reinehr et al [27] have shown in p47 phox knock-out mice that hepatocytes no longer produced ROS. Furthermore, Heymes et al [28] found an increase in translocation of p47 phox to the sarcolemmal membrane of cardiomyocytes in failing human hearts compared to non-failing hearts, which coincided with increased membrane and intracellular gp91 phox expression, analyzed by immunohistochemistry, which could suggest that both p47 phox and gp91 phox are necessary for cardiomyocyte damage.…”
Section: Discussionmentioning
confidence: 99%
“…Bafilomycin A1 reduced the hypertonicity-induced pH L decrease by about 50%. Previous studies in rat hepatocytes (Schreiber et al, 1994;Reinehr et al, 2006) have shown similar pH L acidification in response to exposure to hypertonic conditions. This acidification was also sensitive to V-ATPase inhibition by bafilomycin A1 (Reinehr et al, 2006), but not by concanamycin A (Schreiber et al, 1996).…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies in rat hepatocytes (Schreiber et al, 1994;Reinehr et al, 2006) have shown similar pH L acidification in response to exposure to hypertonic conditions. This acidification was also sensitive to V-ATPase inhibition by bafilomycin A1 (Reinehr et al, 2006), but not by concanamycin A (Schreiber et al, 1996). In the study of Reinehr and colleagues, the effect of hypertonicity on pH L was removed at a bafilomycin A1 concentration of only 0.1 μmol l -1 (Reinehr et al, 2006).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations